A Stability Enhancement Method for Centrifugal Compressors using Active Control Casing Treatment System. Issue 1 (July 2015) - Zhao, Yuanyang; Xiao, Jun; Li, Liansheng; Yang, Qichao; Liu, Guangbin; Wang, Le
Abstract: The centrifugal compressors are widely used in many fields. When the centrifugal compressors operate at the edge of the surge line, the compressor will be unstable. In addition, if the centrifugal compressor runs at this situation long time, the damage will be occurred on compressor. There are some kinds of method to improve and enlarge the range of the centrifugal compressors, such as inlet guide vane, and casing treatment. For casing treatment method, some structures have been researched, such as holed recirculation, basic slot casing treatment and groove casing treatment. All these researches are the passive methods. This paper present a new stability enhancement method based Active Control Casing Treatment (ACCT). All parts of this new method are introduced in detail. The control strategy of the system is mentioned in the paper. As a research sample, a centrifugal compressor having this system is researched using CFD method. The study focuses on the effect of the active control system on the impeller flow. The vortex in impeller is changed by the active control system. And this leads to the suppression of the extension of vortex blockage in impeller and to contribute to the enhancement of the compressor operating range.